1151 MYOCARDIAL VIABILITY IN PATIENTS WITH ISCHEMIC LEFT VENTRICULAR DYSFUNCTION: A CARDIAC MAGNETIC RESONANCE SINGLE-CENTRE EXPERIENCE. (15th December 2022) - Donato, Filippo; Cardaioli, Francesco; Zuccarelli, Vittorio; Porcelli, Giorgio; La Commare, Marina; Fovino, Luca Nai; Tarantini, Giuseppe; Marra, Martina Perazzolo; Iliceto, Sabino; Cipriani, Alberto; Lorenzoni, Giulia
Abstract: Background: Whether assessment of myocardial viability (MV) by delayed enhancement cardiac magnetic resonance (DE-CMR) can help identify patient with severe ischemic left ventricular (LV) disfunction who might benefit from coronary revascularization has not been yet clearly established. Moreover, although improvement in LV function is one of the heart failure treatment goal, its prognostic implication remains controversial. Methods: We retrospectively evaluated all consecutive patients with a LV ejection fraction (EF) of 35% or less and extensive coronary artery disease undergoing DE-CMR for assessment of MV in our Department from November 2013 to December 2020. DE-CMR was routinely prescribed before any heart team indication, either coronary intervention (surgical or percutaneous) plus optimal medical therapy (OMT) or OMT only. Quantification of DE was determined visually by comparing the ratio of the thickness of infarcted myocardium to that of total wall thickness within a given segment. A dysfunctional segment (hypokinetic/akinetic) was considered viable when DE transmurality was ≤50%. Accordingly, a patient was considered to have MV when ≥4 dysfunctional but viable segments were present. The primary end point was death from any cause. Secondary end point was improvement in LVEF during follow-up, defined as an increase in LVEF class compared to baseline. Results: Of the 70 patients (64 males, median age 67 years [62-75], median LVEF 27% [21-30]) enrolled, 46 (66%) underwent coronary revascularization, of which 16 with surgery and 30 with percutaneous intervention. Only 16 procedures were considered complete, fully revascularizing all diseased vessels and dysfunctional segments. The baseline clinical characteristics (including age, diabetes, eGFR, peripheral vascular disease, LVEF, LV end diastolic volume, and Syntax score) of revascularized patients did not differ significantly to those receiving OMT only, except for number of viable segments, which were significantly higher in patients undergoing revascularization (p=0.017). Over a median follow-up of 31 months (18-45), 15 patients (21%) died. Revascularization plus OMT was associated with a lower incidence of death from any cause than OMT only group (hazard ratio, 0.26; 95% CI 0.09-0.74; p=0.01). However, no significant interaction was observed between the presence/absence of MV and the beneficial effect of revascularization (p=0.39). Improvement in LVEF was observed only among patients with MV, irrespective of treatment assignment (p=0.02). However, survival did not differ significantly between patients who had improvement in LVEF from those who did not have such improvement (logRank p=0.81) Conclusion: Among patients with severe ischemic LV systolic dysfunction, coronary revascularization plus OMT was beneficial in prolonging survival, compared to OMT only. However, this beneficial effect was not driven by MV. Furthermore, although increase in LVEF was more likely to occur among patients with MV, such improvement was not related to long-term survival.